2000
DOI: 10.1007/bf02236987
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent expressions of metallothionein, glutathione S-transferase-π, and P-glycoprotein in colorectal cancers

Abstract: The patients with concurrent expression of drug-resistant proteins in their cancers had worse prognoses. Examining drug-resistant proteins in colorectal cancers may be useful in selecting adjuvant chemotherapy and in predicting prognosis more accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…However, to date, only limited information is available regarding the role of MT in colorectal carcinoma patients [13, 14, 15]. Öfner et al [13]reported that only 24% of the patients with Dukes D colon carcinoma were positive for MT and almost a similar percentage (21%) of patients were found to be positive in our patients.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, to date, only limited information is available regarding the role of MT in colorectal carcinoma patients [13, 14, 15]. Öfner et al [13]reported that only 24% of the patients with Dukes D colon carcinoma were positive for MT and almost a similar percentage (21%) of patients were found to be positive in our patients.…”
Section: Discussionmentioning
confidence: 83%
“…It was considered as an important mechanism during tumor progression and appears to be predominantly correlated with more advanced, highly malignant tumors [11, 12]. However, to date only limited information is available regarding the role of MT in the pathogenesis of colorectal cancer and drug resistance in colorectal cancer patients [13, 14, 15]. In the present study, we have investigated MT expression in primary colorectal tumors and their corresponding liver metastatic lesion by immunohistochemistry, and have addressed whether MT expression at these two sites could affect the prognosis and drug resistance potential with regard to cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…In CRC, several reports have studied MT1 + 2 immunohistochemical expression, showing that MTs are heavily down-regulated in this tumor type. However, its association with patient prognosis is far from clear, with most reports showing a lack of correlation between MT and OS and DFS [17][18][19][20]. Ofner et al [21], however, report a statistically significant association of these variables with lower MT levels, whereas another study associated higher MT expression with worse prognosis, although the number of cases was low [22].…”
Section: Discussionmentioning
confidence: 93%
“…In most of the cases high level of the protein was linked to poor prognosis. Several authors showed an evident relationship between intensity of MT expression and clinical advancement of the tumours, frequency of metastasis development, as well as shortening of survival rate and disease free survival [17,28,[31][32][33][34]. In some tumours also a significant correlation between high levels of MT and unfavourable results of treatment was observed [30,35,36].…”
Section: Discussionmentioning
confidence: 99%